Prevention of irreversible aggregation of whey soy proteins in their foam fractionation from soy whey wastewater. Issue 5 (4th April 2016) - Li, Rui; Wu, Zhaoliang; Wang, Yanji; Ding, Linlin; Liu, Wei
Abstract: Prevention of irreversible aggregation of whey soy proteins (WSP) in their foam fractionation from soy whey wastewater is important for achieving their large‐scale recovery. For effectively preventing the irreversible aggregation of WSP, this work studied its dependencies on the WSP enrichment ratio and the height of the collected foam which freely collapsed. The results show that most insoluble aggregates formed in the desorption of WSP from the gas–liquid interface, and their formation was closely related to their high local enrichment in the foam. Based on the above results, a chemical defoaming agent with 25% Tween 20 was developed to reduce the relative content of insoluble aggregates in the foamate and the decrease reached about 80%, compared to the case without Tween 20. The prevented irreversible aggregation effectively improved food‐related properties of the WSP product. Copyright © 2016 Curtin University of Technology and John Wiley & Sons, Ltd.